2007
DOI: 10.1001/archpedi.161.8.798
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Identification of, Advocacy for, and Intervention in Neurocognitive Problems in Survivors of Childhood Cancer

Abstract: With modern therapies and supportive care, survival of childhood cancer has increased considerably. Patients who have survived cancers involving the central nervous system or who have received therapy toxic to the developing brain are at risk of long-term neurocognitive sequelae. Negative outcomes are observed most frequently in survivors of acute lymphoblastic leukemia and brain tumors. The Children's Oncology Group Long-term Follow-up Guidelines Task Force on Neurocognitive/Behavioral Complications After Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
183
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(204 citation statements)
references
References 74 publications
13
183
1
7
Order By: Relevance
“…Our findings are consistent with those of a recently published study that found over 90% of Latino parents of childhood cancer survivors expressed interest in a culturally competent intervention aimed at reducing neurocognitive late effects [9]. Our intervention is based on the premise that neurocognitive assessment should be a standard component of survivorship care for at-risk patients, and that it plays a crucial role in addressing immediate school needs, as well as longer-term educational, vocational, and employment outcomes [2][3][4]10]. We believe that the critical ingredient of our approach is its culturally competent design and implementation (Table S1), which includes a culturally and linguistically competent psychologist.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings are consistent with those of a recently published study that found over 90% of Latino parents of childhood cancer survivors expressed interest in a culturally competent intervention aimed at reducing neurocognitive late effects [9]. Our intervention is based on the premise that neurocognitive assessment should be a standard component of survivorship care for at-risk patients, and that it plays a crucial role in addressing immediate school needs, as well as longer-term educational, vocational, and employment outcomes [2][3][4]10]. We believe that the critical ingredient of our approach is its culturally competent design and implementation (Table S1), which includes a culturally and linguistically competent psychologist.…”
Section: Discussionsupporting
confidence: 87%
“…Although approximately 90% of patients become long-term survivors, up to 40% may develop treatment-related neurocognitive dysfunction that impairs learning and school performance [1][2][3]. Consequently, routine neuropsychological screening is recommended by the Children's Oncology Group (COG Long-Term Follow-Up Guidelines) for all childhood ALL survivors [4]. However, low socioeconomic status (SES) is associated with lower cognitive and academic functioning [5] and is hypothesized to exacerbate treatment-related neurocognitive deficits [6].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsihološka procena prema navedenim preporukama podrazumeva procenu inteligencije, brzinu procesiranja, akademsko postignuće, pamćenje, pažnju i koncentraciju, vizuo-motornu i vizuospacijalnu organizaciju, verbalnu fluentnost, egzekutivne funkcije i planiranje (2). Cilj neurospihološke procene je utvrđivanje neurokognitivnih deficita zbog organizovanja neurokognitivne rehabilitacije kroz individualne programe intervencija, zatim specifične edukativne planove i eventualno primenu hitnih intervencija koje podrazumevaju i uključivanje psihofarmaka (na primer methylphenidate) [16,48]. U nekoliko studija je ispitivana efikasnost farmakoloških stimulansa u unapređenju neurokognitivnih funkcija kod dece lečene od tumora CNS-a.…”
Section: Neurokognitivne Posledice Tumora Cns-a Kod Dece I Mladihunclassified
“…However, the combination of different modalities of treatment that promote the efficacy of therapies can also elicit adverse physical, cognitive, emotional, and social conditions, which are attributed to the aggressiveness of the therapies and the neoplasia itself (Nathan et al, 2007).…”
Section: Cns Tumors In Children Have Peculiar Characteristicsmentioning
confidence: 99%